2019
DOI: 10.1093/jme/tjz148
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Frequency of the kdr Mutation V410L in Natural Populations of Aedes aegypti (L.) (Diptera: Culicidae) From Eastern and Southern Mexico

Abstract: Aedes aegypti (L.) is the primary vector of the viruses that cause dengue, Zika, and chikungunya, for which effective vaccines and drugs are still lacking. Current strategies for suppressing arbovirus outbreaks based on insecticide use pose a challenge because of the rapid increase in resistance. The widespread and excessive use of pyrethroid-based insecticides has created a large selection pressure for a kdr-type resistance, caused by mutations in the para gene of the voltage-gated sodium channel (vgsc). Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…A total of 12 genotypes were obtained and validated in the populations analyzed, using multiplex PCR and the individual endpoint technique previously reported by Saavedra et al [10], Yanola et al [24] and Villanueva-Segura et al . [15], demonstrating that all samples had the same genotype using multiplex PCR as with AS-PCR (Tables 2 and 3).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…A total of 12 genotypes were obtained and validated in the populations analyzed, using multiplex PCR and the individual endpoint technique previously reported by Saavedra et al [10], Yanola et al [24] and Villanueva-Segura et al . [15], demonstrating that all samples had the same genotype using multiplex PCR as with AS-PCR (Tables 2 and 3).…”
Section: Resultsmentioning
confidence: 98%
“…For the validation of the results obtained in multiplex PCR, AS-PCR was performed according to Saavedra et al [10], Yanola et al [24] and Villanueva-Segura et al [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 12 genotypes were obtained and validated in the populations analyzed, using multiplex PCR and the individual endpoint technique previously reported by Saavedra et al [10], Yanola et al [24] and Villanueva-Segura et al [15], demonstrating that all samples had the same genotype using multiplex PCR as with AS-PCR (Tables 2 and 3 (Table 3).…”
Section: Multiplex Pcr Vs As-pcr Assaymentioning
confidence: 98%
“…Later, Villanueva-Segura et al reported high allelic frequencies of L410 in 25 populations of Ae. aegypti occurring in 2018 in eastern and southernMexico with frequencies of 0.10-0.99[15].…”
mentioning
confidence: 99%